The role of issue linkage in managing the Mekong - Kim Hang Pham Do (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The Mekong River is the major water source in Southeast Asia and shared by six countries. There is a rush to acquire sources of alternative energy and other benefits to meet the growing demand for water and energy, while China and Myanmar have refused to cooperate fully in the Mekong River Comission, leading to increase risks within the region. Development of the water resources of the Mekong River Basin is the subject of intense debate both within the Mekong region and internationally. This paper investigates the concept of issue linkage to resolve unidirectional externalities in the Mekong River. Using linked games, the paper shows that the downstream nations can consider the use of linkage as a form of side payment in achieving a basin-wide agreement. This analysis supports the integrated water resource management-based Basin Development Strategy adopted by the Mekong River Commission in April 2011 for managing the region's sustainability development.
Keywords: C71; C72; D62; 330; transboundary water resources; Mekong River Basin; externality games; issue linkage; cooperative solution